Intelligent Freeform Deformation for LED Illumination Optics - Samji Isaac Chandra, Annie Shalom (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2018)
In freeform optics, the optimization is limited due to large number of parameters present in it. This limitation was overcome by a technique known as optimization using freeform deformation (OFFD). Though this technique proved to work well, it has left many challenges to the optical designer. These challenges are solved by providing mathematical design techniques. This implementation transformed the OFFD into an intelligent tool replacing the optical designer's efforts during the design process.